Analisis Pengelolaan Keuangan Desa Berdasarkan Peraturan Menteri Dalam Negeri Nomor 20 Tahun 2018 (Studi Kasus Pada Desa Junjung Kecamatan Sumbergempol Kabupaten Tulungagung) - Fahira Divanka Syahrani; Faizal Satria Desitama (Jurnal Ilmiah Wahana Pendidikan, 2023)
In the Regulation of the Minister of Home Affairs Number 20 of 2018 concerning Village Financial Management, the rules for managing village funds are controlled by simple, responsible and inclusive standards and carried out in an organized and financial manner. The Corruption Eradication Commission (KPK) noted that there were 601 cases related to misappropriation of village funds that were uncovered from 2012 to 2021. The type of research used in this research is qualitative research using a descriptive approach and very in-depth exploration. data collection techniques used in the form of interviews and observation and documentation. Obtain primary data in the form of details of the village budget and secondary data in the form of budget realization reports, reports on changes to the village income and expenditure budget. The purpose of this study was to find out and describe the process of implementing Junjung village financial management based on Minister of Home Affairs Regulation No. 20 of 2018. Furthermore, to find the truth regarding the problems that exist in Junjung village, especially in the financial management of Junjung village. The results showed that in the process of managing village finances in Junjung Village, there was an inappropriate assessment at the planning stage at point 4, at the first point at the administration stage, and at the accountability stage at point 3. Neutral ratings were only found at the implementation stage at point 1 to 4 And besides those mentioned above, it is in accordance with the Minister of Home Affairs Regulation number 20 of 2018.